Tensile deformation behavior and strengthening mechanism of a Fe2.5Ni2.5CrAl multi-principal element alloy - Ling Qiao; R.V Ramanujan; Jingchuan Zhu (Materials & Design, 2023)
The microstructure and tensile deformation behavior of a Fe2.5Ni2.5CrAl multi-principal element alloy (MPEA) were investigated. The combined effect of the soft FCC phase and the hard BCC + B2 microconstituent resulted in a best-in-class strength-ductility combination. The stress–strain relationship obtained from nano-indentation tests agrees well with the tensile stress–strain curves. The fracture surface of Fe2.5Ni2.5CrAl MPEAs indicates the ductile fracture. Cracks tend to form at the interfaces of the FCC/BCC phases and expand along the voids by plastic deformation. Both dislocations and deformation twinning were responsible for the excellent properties. Second phase strengthening resulted in the largest strength increment. MD simulations revealed the formation of the HCP structure and stacking faults. Shockley dislocations were the key factor in the deformation behavior. Our study has shown best-in-class strength-ductility combination in a commercially relevant multi principal element alloy, the results are promising for several industrial applications.